Socio-Cultural factors that influence the ways B-Tech students think about referencing and related concepts as a literacy practice - Mbutho, Nozuko Princess (School of Education, 2020)
The literature shows that many university students, both globally and in South Africa, do not understand what fully constitutes referencing and why referencing is important in their scholarly journey and in academic institutions. As a result students neglect referencing in their academic work. It has been documented that poor referencing practices, or lack of referencing, might contribute to the persistent rise of plagiarism in higher educational institutions all over the world. I have observed similar trends among our B-Tech students at the University of Technology where I lecture. B-tech students seem to battle to understand the importance of referencing and as a result their assignments are not referenced even though students have been at the university for more than three years. These observations spiked an interest in me to explore the reasons behind this persistent issue. Therefore the aim of this study was to investigate the socio-educational and cultural factors that might influence the way students think about referencing and related practices beyond textual issues. The main reason for looking at these socio-educational and cultural factors is related to the South African diverse cultural and educational context. South Africa has eleven official languages, varied cultural beliefs and value systems, wide-ranging schooling systems in spite of the demise of apartheid, and its people have different socio-economic statuses, and political interests. Therefore, I considered that these differences need to be taken into consideration when dealing with issues of unintentional plagiarism and poor referencing skills in universities. After ethical approval, fifteen third year and B-Tech (fourth year) students from one of the University of Technology (UOT) campuses in South Africa, and with varied cultural value systems, varied educational schooling backgrounds, and varied home language backgrounds were chosen to participate in the study, using a heterogeneous purposeful sampling technique. Data were collected using face-to-face in-depth semi-structured interviews. Transcripts from the interviews were analysed using elements of Grounded theory. The results show that, despite their different cultural and schooling backgrounds, the majority of the students in the sample had never been exposed to formal instruction on referencing skills in high school. Their first formal referencing training was at the university. The students felt that the training provided at our UOT was not in-depth, practical or extensive enough. Furthermore the students reported that the reading and writing practices in high school were limited to memorising and regurgitating chunks of text from authoritative texts without necessarily being encouraged to acknowledge sources of information. The students were used to being given all the information considered necessary by teachers in class, and therefore saw no need to search for information themselves. Based on these findings, the following recommendations are suggested: lecturers at our and other higher education institutions need to be cognisant that critical reading and writing, referencing and its related practices might be an unknown concept and practice for new students joining the university. Lecturers therefore need to provide a more detailed and comprehensive training on referencing and its related concepts. In addition, higher educational institutions should provide extensive training for lecturers on referencing, on how to teach referencing, and how to provide informative and developmental feedback to the students.